2020
DOI: 10.7717/peerj.8669
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and toxicity of clothianidin to monarch butterflies from milkweed consumption

Abstract: Recent concern for the adverse effects from neonicotinoid insecticides has centered on risk for insect pollinators in general and bees specifically. However, natural resource managers are also concerned about the risk of neonicotinoids to conservation efforts for the monarch butterfly (Danaus plexippus) and need additional data to help estimate risk for wild monarch butterflies exposed to those insecticides. In the present study, monarch butterfly larvae were exposed in the laboratory to clothianidin via conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 44 publications
2
28
2
Order By: Relevance
“…However, clothianidin had relatively weak effects at both concentrations for all variables measured, with a moderate and only marginally significant reduction in survival at the maximum concentration tested. While our statistical power to tease apart relatively minor differences in mortality was low, this outcome corresponds closely with data reported by Bargar et al 47 who calculated clothianidin LC 50 values ranging from 47 to 205 ng/g for monarchs experiencing chronic exposure over their entire larval period, and Krishnan et al 45 who reported a range of 800-7,800 ng/g for acute exposure across instars. Given that 56.55 ng/g was the maximum value we ever recorded in > 1,000 milkweed leaf samples at multiple sites over 2 years 52 and other studies reported even lower maximum concentrations (4.02 ng/g in field samples in South Dakota 46 ), we consider it unlikely that clothianidin is a major driver of monarch declines.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, clothianidin had relatively weak effects at both concentrations for all variables measured, with a moderate and only marginally significant reduction in survival at the maximum concentration tested. While our statistical power to tease apart relatively minor differences in mortality was low, this outcome corresponds closely with data reported by Bargar et al 47 who calculated clothianidin LC 50 values ranging from 47 to 205 ng/g for monarchs experiencing chronic exposure over their entire larval period, and Krishnan et al 45 who reported a range of 800-7,800 ng/g for acute exposure across instars. Given that 56.55 ng/g was the maximum value we ever recorded in > 1,000 milkweed leaf samples at multiple sites over 2 years 52 and other studies reported even lower maximum concentrations (4.02 ng/g in field samples in South Dakota 46 ), we consider it unlikely that clothianidin is a major driver of monarch declines.…”
Section: Discussionsupporting
confidence: 89%
“…Overall, our data point to several key messages. First, based on the results from this experiment combined with several other recently published studies 45,47,52,75 , it seems unlikely that neonicotinoids are one of the primary drivers of monarch declines. This is not to say that neonicotinoids are completely innocuous, but compared with other ongoing threats (e.g., loss of milkweed host-plants and overwintering habitat), they likely play a secondary role.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The proposed method allows for the quantification of the compounds in a single run at sub-ng/g concentrations using a faster and/or more sensitive method than those found in the literature [12][13][14]17,22,23,[26][27][28]. The method can quantify specific analytes in a mixture of neonicotinoids at trace levels in small quantities of milkweed leaf and pollen to facilitate exposure assessment for honey bees, native bees, and monarch butterflies [12,18,19,29].…”
Section: Discussionmentioning
confidence: 99%
“…To date, extraction of neonicotinoids from plant leaf tissues, specifically milkweed leaf tissue, is labor-intensive and involves complicated clean-up steps [16,[18][19][20][21]. These methods use various components, such as Celite, C 18 cartridges, concentration steps, sodium chloride, anhydrous magnesium sulfate, filtration, and solvent exchange.…”
Section: Plant Tissue Matrixmentioning
confidence: 99%